Ecological level analysis of primary lung tumors in dogs and cats and environmental radon activity. (3rd November 2020) - Fowler, Brittany L.; Johannes, Chad M.; O'Connor, Annette; Collins, Deanna; Lustgarten, Jonathan; Yuan, Chaohui; Weishaar, Kristen; Sullivan, Kelly; Hume, Kelly R.; Mahoney, Jennifer; Vale, Brittany; Schubert, Alicia; et al.
Abstract: Background: Epidemiologic studies suggest residential radon exposure might increase the risk of primary lung cancer in people, but these studies are limited by subject mobility. This limitation might be overcome by evaluating the association in pets. Hypothesis: Primary pulmonary neoplasia (PPN) rate is higher in dogs and cats residing in counties with a high radon exposure risk (Environmental Protection Agency [EPA] zone 1) compared to zones 2 (moderate radon exposure risk) and 3 (low radon exposure risk). Animals: Six hundred ninety client‐owned dogs and 205 client‐owned cats with PPN. Methods: Retrospective review of medical records at 10 veterinary colleges identified dogs and cats diagnosed with PPN between 2010 and 2015. Each patient's radon exposure was determined by matching the patient's zip code with published county radon exposure risk. County level PPN rates were calculated using the average annual county cat and dog populations. The PPN counts per 100 000 dog/cat years at risk (PPN rates) were compared across radon zones for each species. Results: The PPN rate ratio in counties in high radon zone (1) was approximately 2‐fold higher than in counties in lower radon zones for dogs (rate ratio zone 1 to 2, 2.49; 95% confidence interval [CI], 1.56‐4.00; rate ratio zone 1 to 3, 2.29; 95% CI, 1.46‐3.59) and cats (rate ratio zone 1 to 2, 2.13; 95% CI, 0.95‐4.79; zone 1 to 3, 1.81; 95% CI, 0.9‐3.61). Conclusions and Clinical Importance: Exposure to household radon might play a role in development of PPN in dogs and cats.